Minimização de perdas de um motor de indução acionado porestratégia de controle preditivo de torque e fluxo - Graciola, Clayton Luiz (2025)
Induction motors are widely employed in various industrial applications and account for a significant share of global energy consumption. In many of these applications, the motors operate under load conditions below nominal, which directly compromises their energy efficiency. Thus, this work presents an alternative control methodology for three-phase induction motors aimed at improving efficiency during operation, based on predictive control. The study begins with simulations using the mathematical model of the induction motor, evaluating different operating points defined by load torque and speed. The results consist of a comparison of the efficiency gains provided by different control strategies over a wide operating range. The optimization potential of efficiency is evidenced by model-based predictive control strategies, through the optimized selection of the flux reference, both in predictive torque control and in predictive current control. Predictive torque control presents more robust dynamic performance, reaching maximum efficiency without compromising system response. In the next stage, the choice of design parameters and the optimization strategy are defined, and the practical implementation of predictive torque and flux control is carried out on a machine test bench, with the acquisition of experimental results. A loss minimization strategy is developed based on an online search method, capable of continuously optimizing efficiency and maintaining robustness against variations in mechanical load and speed reference. Experimental data demonstrate a potential efficiency gain of up to 39.06% for the induction motor operating under light load conditions